2014
DOI: 10.4314/bajopas.v7i1.16
|View full text |Cite
|
Sign up to set email alerts
|

<b>Mineral Elements Content of some Coarse Grains used as staple Food in Kano Metropolis, Nigeria</b>

Abstract: Analysis of mineral elements were carried out on some coarse grains used as staple food in Kano metropolis. The levels of Magnesium, Calcium, Manganese, Iron, Copper and Zinc were determined using atomic absorption spectrophotometer (AAS), and that of Sodium and Potassium were obtained using flame photometer (FES). The result of the study shows that the mean results of the mineral elements ranged in mg/kg from 62.50±0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Wheat appeared to be rich in manganese and potassium (28.39 and 957.19 µg/g), red sorghum rich in copper (5.14 µg/g) and yellow maize rich in zinc and calcium (5.93 and 1004.69 µg/g). The observed variations were in agreement with the work of Mohammed and Ahmad (2014). However, ANOVA comparing the concentrations of all minerals in each of the samples of grain analysed revealed that there was no statistical difference in their mineral contents, thus implying that all grains have statistically comparable mineral content irrespective of their type.…”
Section: Mineral Content Of Grainssupporting
confidence: 89%
“…Wheat appeared to be rich in manganese and potassium (28.39 and 957.19 µg/g), red sorghum rich in copper (5.14 µg/g) and yellow maize rich in zinc and calcium (5.93 and 1004.69 µg/g). The observed variations were in agreement with the work of Mohammed and Ahmad (2014). However, ANOVA comparing the concentrations of all minerals in each of the samples of grain analysed revealed that there was no statistical difference in their mineral contents, thus implying that all grains have statistically comparable mineral content irrespective of their type.…”
Section: Mineral Content Of Grainssupporting
confidence: 89%
“…The results showed that the average Ca content in this study is greater than in previous reports. For instance, Mohammed and Ahmad (2014), Ullah (2010), and Gara et al (2013), reported that the Ca amount in maize ranged from 70.00-186.67 mg/kg, 66.5-104 mg/kg), 410-590 and 321.7-789.1mg /kg, respectively.…”
Section: Comparison Of Individual Nutrients In Maize Sample Calcium (Ca)mentioning
confidence: 99%
“…Surveying in China performed by collecting 438 wheat grain samples from two regions that were categorized on soil pH (non-acid pH>7, and acid pH<7), showed that the average concentration of Mn was 43.7 mg kg -1 (ranging from 13.9 to 98.3 mg kg -1 ) (Shi et al, 2020). Average concentrations in (mg kg −1 ) of 13.0 for Mn and 66.7 for Fe in wheat grain reported by (Mohammed and Ahmad, 2014). In different countries, the concentration of Fe in wheat grain ranged between 23.0 and 73.0 mg kg -1 (Melash et al, 2016).…”
mentioning
confidence: 99%